Blood supply strategies facing a reference blood centre in Brazil during the COVID‐19 pandemic. (2nd June 2020) - Barjas‐Castro, Maria de Lourdes; Baumgartner, José Eduardo; Sales, Leandro N. M.; Santos, Roberta A.; Pereira, Fabrício B.; Castro, Vagner
Abstract : Background: The SARS‐CoV‐2 pandemic is having an impact on blood supply. This situation has led to new strategies to minimize the impact on blood product availability. Methods: The Hemocentro UNICAMP, a regional reference centre in Brazil, has established availability strategies, respecting national and local measures to decrease transmission of SARS‐CoV‐2. Measures include booking donation appointments, reorganization of areas to permit social distancing, a pre‐reception to reinforce donor instructions, antisepsis of donors' hands with 70% gel alcohol at each step of the process, post‐donation information (PDI) reinforcement, recruitment intensification using social media/mass media, rapid replacement of cancelled mobile collections, reinforcement of collection from army units. Rational blood use was reinforced in hospitals, elective procedures were suspended and stricter blood distribution was adopted. Results: A median increase of 14·5% was obtained in weekly blood donations, versus pre‐crises period (1338 vs 1169) and a 15·9% decrease in blood distribution (1312 vs 1103 red blood cell units) ( P < 0·0001, χ 2 = 28·8). Booked appointments corresponded to 42·2% of all donations made in the period, with a mean absence of 19% at bookings. Mobile unit blood collections cancelled in the period were 8/25 per month (vs. around 3/25 before). About 62% of the cancelled mobile collections could be replaced. Mean PDI increased from 5/week vs. 2/week in the previous period. Conclusion: The strategy proved successful, although questions about the best approach to maintain blood supply during the COVID‐19 pandemic remain. Such experiences may help blood centres to design strategies to maintain blood stores during pandemic situations in the future.